Classification of Ordered Type Soliton Metric Lie Algebras by a Computational Approach - Kadioglu, Hulya (HINDAWI LTD, 2013)
We classify some soliton nilpotent Lie algebras and possible candidates in dimensions 8 and 9 up toisomorphy. We focus on 1 < 2 < ... < n type of derivations, where n is the dimension of the Lie algebras. We present algorithms to generate possible algebraic structures.
Keywords: EINSTEIN SOLVMANIFOLDS; Mathematics